2021
DOI: 10.1111/jne.13041
|View full text |Cite
|
Sign up to set email alerts
|

The psychological impact of COVID‐19 pandemic on patients with neuroendocrine tumors: Between resilience and vulnerability

Abstract: The COVID-19 pandemic has added another layer of complexity to the fears of patients with neuroendocrine tumors (NETs). Little is known regarding the psychological impact of the COVID-19 outbreak on patients with gastroenteropancreatic or bronchopulmonary (BP) NETs. We longitudinally surveyed the mental symptoms and concerns of NET patients during the plateau phase of the first (W1) and second epidemic waves (W2) in Italy. Seven specific constructs (depression, anxiety, stress, health-related quality of life, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 47 publications
(71 reference statements)
0
2
0
Order By: Relevance
“…Interestingly, the prevalence of anxiety and depression also seems to increase over the course of the pandemic waves. In an Italian study by Lauricella, this effect was shown within the 1st and 2nd pandemic waves for NET patients [24]. Since our survey was conducted during the 3rd wave, the higher rates of psycho-emotional distress can be better explained.…”
Section: Discussionmentioning
confidence: 77%
“…Interestingly, the prevalence of anxiety and depression also seems to increase over the course of the pandemic waves. In an Italian study by Lauricella, this effect was shown within the 1st and 2nd pandemic waves for NET patients [24]. Since our survey was conducted during the 3rd wave, the higher rates of psycho-emotional distress can be better explained.…”
Section: Discussionmentioning
confidence: 77%
“…First, given the possible persistence of the pandemic, the decrease of surgical volumes could potentially lead to the diagnosis of a higher rate of advanced stage diseases in the future. Second, delays in initiating treatment of patients well known to already experience long diagnostic delays, 20 may have a profound psychological impact. In this regard, recent evidence has already shown a surge in depression and anxiety rates among NET patients subsequent to the initiation of the COVID‐19 outbreak 21 .…”
Section: Discussionmentioning
confidence: 99%